Structure‐Guided Engineering of Cytotoxic Cabazitaxel for an Adaptive Nanoparticle Formulation: Enhancing the Drug Safety and Therapeutic Efficacy. (9th November 2018) - Wan, Jianqin; Qiao, Yiting; Chen, Xiaona; Wu, Jiaping; Zhou, Liqian; Zhang, Jun; Fang, Shijiang; Wang, Hangxiang
Abstract: Development of a sophisticated nanotherapeutic platform to deliver potent agents effectively and safely to desired tumor sites remains challenging. Cabazitaxel (CTX) holds particular interest for clinical use because of its ability to overcome the drug resistance caused by other taxane drugs. However, investigations of this potent agent have been met with only limited success due to its high toxicity in patients, and thus the exploration of CTX as a safe chemotherapeutic remains a tremendous challenge. Here, it is reported that CTX can be structurally tailored to make it more compatible with a polymeric platform through chemical derivatization with oligolactide (oLA). Covalent conjugation of CTX to oLAs yields new entities that are sufficiently miscible with exogenous polymer matrices to form injectable nanomedicines (termedo(LA) n ‐CTX‐NPs ). Utilizing theseo(LA) n ‐CTX‐NPs, the remarkable increases in tumor accumulation and amelioration of drug toxicity in animals are demonstrated. In a xenograft model of lung cancer, administration ofo(LA)18 ‐CTX‐NPs enhances the antitumor efficacy relative to administration of free CTX. Overall, the data show that precision editing of drug chemical structures can be harnessed to generate better tolerated and more efficient nanomedicines. This approach might be a complementary strategy to simultaneously augment the safety and potency of other anticancer agents. Abstract : Rational engineering of a highly toxic anticancer drug, cabazitaxel, with short oligolactides is presented. The structurally tailored prodrugs are sufficiently miscible and compatible with adaptive polymer matrices, generating injectable nanotherapy with enhanced tolerability and therapeutic efficacy in vivo. The scaffold could have high value as a therapeutic platform to treat patients with taxane‐resistant cancer.